REFLECTION OF THE AUTHORIAL WORLDVIEW IN JACK LONDON’S NORTHERN STORIES (KONFERENSIYA, 2026)
This article examines how Jack London’s worldview is reflected in the cycle of his Northern stories written during and after his experiences in the Yukon. Through close textual analysis of “The Law of Life”, “To Build a Fire”, and “The White Silence”, this study identifies the philosophical and ideological foundations of London’s naturalistic ethos. The discussion demonstrates that London’s worldview integrates naturalistic determinism, existential resignation, and humanistic affirmation of dignity in the face of indifferent nature. Supported by direct textual quotations and existing scholarly research, the article argues that the northern tales constitute a coherent system of moral-philosophical ideas revealing London’s complex attitude toward nature, mortality, and human worth.